Effects of Different Percentages of Blood Flow Restriction on Energy Expenditure - Pfeiffer, Patrick de Souza; Cirilo-Sousa, Maria Socorro; Santos, Heleodório Honorato dos (International Journal of Sports Medicine, 2019)
The study aimed to analyze the effect of different levels of blood flow restriction (BFR) on energy expenditure (EE) and subjective perceptions of discomfort (SPD) during aerobic exercises. A sample group of 24 young men was required to walk on a treadmill for 14 min at 40% of their maximum speed, with 4 different percentages of BFR (0, 50, 80 and 100%) applied in the lower limbs (LL) once a week with a 7-day interval between the 4 evaluations. EE data were collected during the exercise periods; SPD data were collected after the exercises. There was a significant increase in EE at 50, 80 and 100% BFR compared to the condition without BFR, and between 50 and 100% BFR; however, there were no differences between 50 and 80% and 80 and 100% BFR. Discomfort showed a significant increase according to the increase in BFR. During the walking exercises with BFR, the EE strongly increased until 50% of BFR; after this level the additional increases slowed. It can be concluded that when performing aerobic exercises with BFR, there is no need to use BFR levels above 50% to reach satisfying level of EE with only a moderate level of discomfort to the practitioner. This study was registered in the Brazilian Registry of Clinical Trials (REBEC) under number RBR-3XHSJX.
Keywords: aerobic exercise; therapeutic occlusion; energy metabolism; oxygen consumption; exercise